Regionalization and the federative crisis in the context of the Covid-19 pandemic: deadlocks and perspectives - Helena Eri Shimizu; Luciana Dias de Lima; André Luís Bonifácio de Carvalho; Brígida Gimenez Carvalho; Ana Luiza D’Ávila Viana (Saúde em Debate)
ABSTRACT Regional health planning is a complex process conditioned by several factors, among which inequalities and federative relations stand out. In the context of the Covid-19 pandemic, these weaknesses in the federative and regional organization of the Unified Health System (SUS) have been acutely exposed, and accentuated by a scenario of incoordination and dismantlement of the institutional design conceived by the Federal Constitution of 1988. This essay aimed to draw reflections on some strategies built at the municipal, regional and state levels to tackle the pandemic, as a response to the political and institutional crisis, as well as to highlight current and future challenges. The work is based on syntheses of the discussions held during the preparatory workshop and the debate table of the IV Congress on Health Policies, Planning and Management of the Brazilian Association of Collective Health (Abrasco), on the theme of federative relations and regionalization in the scenario of the Covid-19 pandemic. The findings include: a lack of federal protagonism and the construction of delegated autonomy of subnational entities in the pandemic; the importance of some experiences of consortia and new partnerships with society; and the challenges and conditions of a new federative pact and new forms and designs to partner and support the organization of the SUS.